2019
DOI: 10.1111/jpm.12580
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to psychiatry and to mental illness among nursing students: Adaptation and use of two validated instruments in preclinical education

Abstract: Accessible SummaryWhat is known on the subject Stigma towards psychiatry and people with serious mental illness (SMI) is prevalent among healthcare providers and can adversely affect patient care. Internalized stigma among nurses can affect personal self‐care and limit help‐seeking behaviours. Stigma around mental health nursing can adversely affect recruitment into this already underserved field. What the paper adds to existing knowledge This is the first report on the adaptation and use in a nursing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Although we cannot identify which elements of the syllabus specifically contributed toward these changes, we can conclude that (a) this 8-week course improved stigmatized views around mental health in the four areas of attitudes, disclosure, social distance, and willingness to seek help; and (b) the instruments that we selected were psychometrically sensitive to detect such change. It is worth emphasizing both points, as they provide a hopeful counterpoint to earlier views (Sherwood, 2019;Thornicroft et al, 2016), including our own, that "even a strong academic curriculum is not sufficient to change stigmatized perceptions about mental illness, psychiatric care, and mental health nursing as a profession" (Martin et al, 2019). We incorporated visual media in the form of two short, widely available video clips: one representing what patients often say they envision when discussing ECT, and another that accurately portrays both the procedure and the experience from a modern patient perspective.…”
Section: Discussionmentioning
confidence: 94%
“…Although we cannot identify which elements of the syllabus specifically contributed toward these changes, we can conclude that (a) this 8-week course improved stigmatized views around mental health in the four areas of attitudes, disclosure, social distance, and willingness to seek help; and (b) the instruments that we selected were psychometrically sensitive to detect such change. It is worth emphasizing both points, as they provide a hopeful counterpoint to earlier views (Sherwood, 2019;Thornicroft et al, 2016), including our own, that "even a strong academic curriculum is not sufficient to change stigmatized perceptions about mental illness, psychiatric care, and mental health nursing as a profession" (Martin et al, 2019). We incorporated visual media in the form of two short, widely available video clips: one representing what patients often say they envision when discussing ECT, and another that accurately portrays both the procedure and the experience from a modern patient perspective.…”
Section: Discussionmentioning
confidence: 94%
“…In order to define the presence and to fight stigmatizing attitudes in health professionals, several studies were conducted with the involvement of undergraduate students in health degree courses: psychology students [16,26,27], nursing students [28][29][30], medical students [31], and general mental health professional students [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dosage or intensity of the video-intervention might be a determining factor. Other studies showed the benefit of adding a booster (showing the video more than once) [ 30 ]. Failure to show significant reductions in fear and loneliness could be also attributed to inadequate content of the video-based interventions.…”
Section: Discussionmentioning
confidence: 99%